OP0192 DISSECTING THE LONG-RANGE GENE REGULATION OF RHEUMATOID ARTHRITISRISK ENHANCERS AT THE 5Q11 LOCUS USING THE COMPLEMENTARY APPROACHES OF CRISPRA AND CRISPRI. (June 2019) - Duffus, Kate; Gough, Oliver; Orozco, Gisela; Adamson, Anthony; Eyre, Stephen
Abstract : Background: Large-scale genome wide association studies (GWAS) in rheumatoid arthritis (RA) have revealed that the majority of associated risk variants lie in non-coding regions of the genome. For RA it has been demonstrated that risk variants are significantly enriched in T cell specific enhancers. One such susceptibility locus known as 5q11 is the third strongest association with RA. At this locus the lead risk variants lie in two distinct active enhancer elements intronic to the ANKRD55 gene. Previous work using chromatin conformation has shown these enhancers make physical contact with the promoter of IL6ST, 150 kb away on the linear chromosome 1 . Whilst ANKRD55 is a gene of unknown function, IL6ST is part of the IL6R complex which regulates the IL6 signalling pathway. Tocilizumab is already an approved drug for RA, which works against the IL6R. CRISPR is an ideal tool to dissect this enhancer-gene relationship to provide us with empirical evidence that the intronic enhancer within ANKRD55 regulates the expression of IL6ST. Understanding how RA risk genetic background affects gene regulation will give us a better understanding of the underlying biology of the disease and can ultimately be used to help repurpose or discover novel drug therapies. Objectives: To use CRISPR interference (CRISPRi) and CRISPR activation (CRISPRa) to perturb the ANKRD55 intronic enhancer and measure the downstream effect on the expression of IL31RA, IL6ST, ANKRD55 ). Methods: We used dead (dCas9) a modified CRISPR Cas9 enzyme that is catalytically inactive, that precisely targets DNA, but does not cut. Instead, effector molecules are fused to the dCas9 (VP64 for activation and KRAB for repression) to alter the transcription of the targeted genes.Two lead functional risk SNPs at the 5q11 risk locus rs10065637 and rs7731626 (R 2 = 0.4472) lie in two distinct enhancer elements separated by 5.5kb. We designed 4 guides across each enhancer, and transduced a T cell line (Jurkat) using lentiviral delivery; first dCas9-KRAB and dCas9-VP64 and subsequently the pool of guides for each enhancer alongside controls. We cultured the cells until confluent and then sorted the top 60% expression of BFP-GFP (KRAB) or MCherry-GFP (VP64). RNA was extracted and then a qPCR was performed (Quantstudio) for IL31RA, IL6ST and ANKRD55 . Results: In the CRISPRa Jurkat cells the guides targeted to both SNP containing enhancers significantly increased the expression of ANKRD55 : rs7731626 (p=<0.0001) and rs6859219 (p=0.0003) respectively. They also increased the expression of IL6ST rs7731626 (p 0.0023) and rs6859219 (p= 0.01). In CRISPRi Jurkat cells the guides targeted to both SNP containing enhancers significantly decreased the expression of ANKRD55 : rs7731626 (p=<0.001) and rs6859219 p=(0.0071). When guides were simultaneously used for both enhancers rs6859219+rs7731626 there was also a significant decrease in expression of ANKRD55 . (p=<0.0001). Only the pool guides against both enhancers significantly decreased the expression of IL6ST (p=<0.0001). In both systems no significant effect was seen on the expression of IL31RA (Figure 1). Conclusion: Results from CRISPRi and CRISPRa are concordant and support the idea that intronic enhancers within ANKRD55, containing SNPs associated with RA susceptibility, can regulate the expression of both ANKRD55 and also modulate long range gene regulation with IL6ST to influence disease risk. These techniques are crucial to begin to dissect and translate GWAS findings. Reference: [1] Capture Hi-C reveals novel candidate genes and complex long-range interactions. Disclosure of Interests: None declared